SYMBOLIZATION OF WALIKAN LANGUAGES IN TV NEWS PROGRAMS (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This research is aimed at revealing the style of the Walikan language, that exposed in the Kowal Kawil JTV Malang news program. The news presented not only educates the audience, but also provides entertainment with the language used. The program which shows the uniqueness has shown an effort to preserve the values of local wisdom in Malang. Through linear broadcasting presentation techniques, it has also made the news more interesting to enjoyed, and the impact directly provides specific emotional colors. The hidden media tries to interpret the content of the news, and the audience also tries to understand the power hidden behind the text and the visualization of the news. This study uses a critical interpretive approach, by applying the semiotic model to find the peculiarities of symbols and the laws of communication, that govern the formation of certain meanings. The results shows, that the signs and meanings behind the acceptance of symbols can also be interpreted through the prevailing social life by using the concept of langue and parole. Langue demonstrated the existence of a language system and abstraction system, and used collectively which was agreed upon by all media consumers, eventually becoming a guide to the practice of language in a society. Parole is a language practice in the form of individual utterances, so the use of the term applies at one particular time. On this basis it can be concluded, that the news that uses the inverse language is a construction of reality, positioned between the original meaning and the specific importance of the media management.